(untitled) (Journal of Geography and Environmental Management, 2019)
This paper presents an analysis of the atmospheric aridity on the Almaty region based on the calculation of the Ped’ S aridity index according to air temperature and precipitation on seven stations, relatively evenly located in the study area over the summer period from 1986 to 2016. Droughts are dangerous natural phenomena, as they lead to the death of crops in vast areas, the massive loss of livestock due to grass burning, extreme heat, dehydration and reduction of water reserves. All these actions reduce electricity generation disrupt industry, transport, trade and the lack of drinking water causes hunger and death in some areas. During droughts, oil and forest fires occur which reduce the soil-protective role of forests, their water conservation value as well as reduce timber for industry and construction. Droughts intensify the melting of glaciers and create conditions for the formation of glacial mudflows. They also contribute to the drying and grinding of the soil, which in turn leads to its wind erosion. During the period of drought, the upper horizons of permafrost thaw, the groundwater level drops, rivers shallow and lakes, ponds and marshes dry out. Nowadays, droughts do not have such terrible consequences, but require large monetary costs to protect and preserve the crop. In the course of this study, some interesting indicators to characterize droughts obtained the number of cases with droughts of varying intensity, the extreme values of the S index and the catalog of atmospheric droughts S.